Analysis and design of high-efficiency DC-DC converters for portable applications - Li, Yue (Nanyang Technological University, 2023)
This Ph.D. research program pertains to inductive DC-DC buck converters for present- and next-generation portable electronic devices. The general objectives include a comprehensive and critical review of DC-DC buck converters, and the ensuing design, monolithic realization and physical measurement (hence verification) of two proposed DC-DC buck converters. These DC-DC converters are the proposed single-phase and proposed dual-phase converters, whose performance exceeds the state-of-the-art, at least in terms of some performance parameters, including higher power-efficiency over a very wide output current range. For the single-phase DC-DC converter, we propose a burst-mode-only converter whose formidable demands are very high power-efficiency over a very wide output current range, yet with very fast transient response and small inductance. Specifically, in a first application, the power efficiency is >95% over the 10mA-500mA load current range and <15mV undershoot/overshoot with <2μs 1% output settling-time. In a second application, the power efficiency is >~94% between 10mA-1A load current and <12mV undershoot/overshoot with <1μs 1% output settling-time. These attributes are derived by means of an energy-on-demand regulation scheme, and the proposed enhanced current sensor, zero current detector and burst controller. Further, the proposed converter features a customizable maximum output current by appropriately setting the predefined peak inductor current and the inductance. The proposed converter, monolithically realized in 130nmBCDLite, produces 0.6V-1.8V output from 2.5V-4.5V input. The performance of the proposed converter is exemplified by the said first and second applications. When benchmarked against reported designs, the proposed converter is very competitive on the basis of many parameters, including the highest power-efficiency over a very wide current load range, small inductance despite low operating frequency, etc. On the basis of a reported Figure-of-Merit (FoM), it features the highest FoM by a large margin. We also demonstrate that the usual tradeoff between high power-efficiency and fast transients – a limitation in state-of-the-art DC-DC converters – can be decoupled. For the dual-phase DC-DC converter, we propose a converter featuring a peak power-efficiency of 94% and a power-efficiency of >93% over the 10mA-2A output current range, yet with very low hardware overhead. The high power-efficiency is achieved by means of our earlier reported burst-mode-only operation for the single-phase converter. In our now-proposed converter, the output current range is doubled and unlike conventional designs, yet with very little compromise to the power-efficiency. The proposed dual-phase converter features the following attributes over the state-of-the-art. First, with the proposed unified output voltage sensing network for dual-phase architecture, the converter can add/remove phases according to load current demand with no ensuing hardware or power overheads. Second, when both phases of the converter are active, they operate under either one of two proposed phase management modes – free run and pseudo synchronized modes – where no current sharing control is required, thereby further minimizing the hardware overheads. The proposed converter, monolithically realized in 130nmBCDLite process, produces an output voltage of 0.6V-1.8V from an input voltage of 2.5V-4.5V. When benchmarked against state-of-the-art converters, the proposed design features not only the highest peak power-efficiency but also across the entire (1mA-2A) current range, yet with the simplest phase adding/shedding scheme, rendering the lowest hardware overheads. In summary, the proposed single-phase and dual-phase DC-DC buck converters are highly appropriate for present- and next-generation portable devices whose demands include very high power-efficiency over a very wide current range, etc.